Digital Storytelling Research Trends in Indonesia: A Systematic Literature Review - Hidayat, Fahmi; Febriyanti, Emma Rosana (Acitya: Journal of Teaching and Education, 2024)
New technologies have largely brought about positive changes in educational settings, enabling educators to improve their expertise and, consequently, elevate the quality of education. Studies reveal that incorporating these technologies leads to increased student engagement, higher levels of achievement, and greater motivation. Digital storytelling is perceived as an ideal method to meet the learning needs of digital native students while also improving their skills for the 21st century as it can be used as a medium for literacy and creativity. This research was conducted through a library approach, analyzing numerous articles focused on digital storytelling. This systematic literature review aims to provide a comprehensive overview of digital storytelling research in Indonesia, shedding light on emerging trends, challenges, and opportunities in this field. The findings highlight key responsibilities for teachers using digital storytelling, emphasizing the importance of developing technology skills, as well as, it uncovers any shifts in focus over time and highpoints gaps in the existing literature, providing valuable insights for future research directions.